Multi-parametric high resolution ultrasound assessment of tibial nerve in diabetic peripheral neuropathy - Walaa Galal Elsayed; Magdy Settein; Ahmed Mohamed Abd Elkhalek; Ahmed Albehairy; Nehal Tharwat (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Diabetic peripheral neuropathy (DPN) is a common and serious complication of diabetes occurring in about 50% of patients. It serves as a strong risk factor for disabling pain, foot ulcers and amputation that have a negative effect on the life quality and bring a heavy economic burden. Therefore, it is important to early diagnose DPN for taking influential targeted measures and preventing foot ulcers and amputations. The aim of this study was to assess the role of different high resolution ultrasound (HRUS) parameters in diagnosing DPN. Results This study included 60 participants classified into three groups [20 diabetic cases with DPN, 20 diabetic cases without peripheral neuropathy (PN) and 20 age-/sex-matched healthy control]. All cases underwent full clinical and laboratory investigations. HRUS examination including shear wave elastography (SWE) of the tibial nerve was also performed. Our study revealed statistically significant difference as regard maximum thickness nerve fascicles (MTNF) between DPN and control groups (P = 0.005) with a cutoff value of 0.45 mm yielding 85% sensitivity and 75% specificity. As regard nerve cross-sectional area (CSA), there was significant statistical difference between each of the three studied groups. A cutoff value of 17.5 mm2 was excellent in differentiating DPN group from control group with 80% sensitivity and 95% specificity. The highest mean nerve stiffness was noted among DPN group compared to diabetics without PN and control groups with significant statistical difference between each of the studied groups. The mean nerve stiffness was excellent in differentiating DPN group from control group with 100% sensitivity and 100% specificity. There was significant statistical positive correlation between neuropathy disability score and diabetes duration, HbA1c levels, MTNF, nerve CSA and stiffness. Conclusions Multi-parametric HRUS using MTNF, CSA and SWE is a promising quantitative technique that has an excellent additive value to the usual qualitative nerve examination. High image quality, real-time examination, non-invasiveness, low cost, wide availability and multi-parametric assessment make HRUS superior to nerve conduction test. It can serve as an accurate novel technique for screening and early diagnosis of DPN even with normal clinical and nerve conduction studies.